SYNTHESIS OF TITANIA IMPREGNATED ON LTL ZEOLITE - Santika Wirawan, Wahyu
Titania (TiO2) has been normally used to perform high photocatalytic activity. The photocatalyst ability can be improved by the use of LTL zeolite as a host material. In this study, TiO2 impregnated LTL zeolite has been synthesized by hydrothermal method at a temperature of 170 ?C for 4 days. While the impregnation process through the absorption of titania precursor, TiCl4 solution, for 15, 60, and 1440 minutes followed by calcination at 400 ? C for 4 hours. Identification of the structure of LTL zeolite and titania was performed by XRD, while SEM-EDX characterization is used to view the morphology and identification of elements, and nitrogen adsorption isotherm technique used to determine the profile of adsorption, surface area and pore. Analysis of the results showed that the synthesized LTL Zeolite has had a surface area of 116.252 m2 / g, total pore volume of 0.1806 cc / g, and the size of the pore diameter <2 nm and 3-5 nm. Results from impregnating the titania produce LTL zeolite with titania content of <1% by weight of the sample. Impregnation process results in the reduction of surface area and total pore volume as the length of time of immersion. Reduction of pore volume with pore size <2 nm was also observed in zeolite impregnation results especially for soaking 15 minutes. Reduction of surface area and pore volume is made possible due to the closing of the pore by the titania particles, so it can be concluded that the impregnation of titania can be performed on the surface of LTL Zeolite.